Controlled synthesis and size effects of multifunctional mesoporous silica nanosystem for precise cancer therapy - Bin Ma; Lizhen He; Yuanyuan You; Jianbin Mo; Tianfeng Chen (Taylor & Francis Group, 2018)
Nanomaterials-based drug delivery systems display potent applications in cancer therapy, owing to the enhanced permeability and retention effect and diversified chemical modification. In this study, we have tailored and synthesized different sized mesoporous silica nanoparticles (MSNs) through reactant control to investigate the relevancy of nanoparticle size toward anticancer efficacy and suppressing cancer multidrug resistance. The different sized MSNs loaded with anticancer ruthenium complex (RuPOP) and conjugated with folate acid (FA) to enhance the selectivity between cancer and normal cells. The nanosystem (Ru@MSNs) can specifically recognize HepG2 hepatocellular carcinoma cells, thus enhance accumulation and selective cellular uptake. The smaller sized (20 nm) Ru@MSNs exhibit higher anticancer activity against HepG2 cells, while the larger sized (80 nm) Ru@MSNs exhibit higher inhibitory effect against DOX-resistant hepatocellular carcinoma cells (R-HepG2). Moreover, Ru@MSNs induced ROS overproduction in cancer cells, leading to DNA damage and p53 phosphorylation, consequently promoting cancer cells apoptosis. Ru@MSNs (80 nm) also inhibited ABCB1 and ABCG2 expression in R-HepG2 cells to prevent drug efflux, thus overcome multidrug resistance. Ru@MSNs also inhibited tumor growth in vivo without obvious toxicity in major organs of tumor-bearing nude mice. Taken together, these results verify the size effects of MSNs nanosystem for precise cancer therapy.